Reduction-Responsive Codelivery System Based on a Metal-Organic Framework for Eliciting Potent Cellular Immune Response - Yang, Y.; Chen, Q.; Wu, Jian-Ping; Kirk, Brett; Xu, J.; Liu, Z.; Xue, W. (American Chemical Society, 2018)
© 2018 American Chemical Society. Utilizing nanoparticles to deliver subunit vaccines can be viewed as a promising strategy for enhancing the immune response, especially with regard to cellular immunity to fight against infectious viruses and malignant cancer. Nevertheless, its applications are still far from practicality because of some limitations such as high cost, non-biocompatibility, non-biodegradability, and the inefficient stimulation of cytotoxic T lymphocyte (CTL) response. In this study, we use metal-organic framework (MOF) MIL-101-Fe-NH 2 nanoparticles as carriers to fabricate an innovative reduction-responsive antigen delivery system for cotransporting the antigen model ovalbumin (OVA) and an immune adjuvant, unmethylated cytosine-phosphate-guanine (CpG) oligonucleotide. In vitro cellular tests show that the MOF nanoparticles can not only greatly improve the uptake of OVA by the antigen-presenting cells but also smartly deliver both OVA and CpG into the same cell. By feat of the reductively controllable release of OVA and the promoting function of CpG, the delivery system can elicit strong cellular immunity and CTL response in mice. Moreover, the increased frequencies of effector memory T cells inspired by the delivery system indicate that it can induce a potent immune memory response. These results demonstrate that MOF nanoparticles are excellent vehicles for codelivering antigen and immune adjuvant and may find wider applications in biomedical fields.